Unjuk kerja Run-Up dan run-Down pada lereng bertangga - ABBAS, ABBAS ([Yogyakarta] : Universitas Gadjah Mada, 2006)
One of the efforts to protect coastal area is by constructing a structure intended to control and restrain the wave attack. One form of such construction applicable to be developed is step structure that can be used for breakwater and beach wall. Some of the influencing variables for the structure design are wave run-up and run-down. wave run-up can be used as the variable in determining the coast structure crown height and run-down wave influences the structural damage. The objective of this study is to identify the run-up and run-down performance on the step gradient. In addition, this study also analyzes the relation between the wave parameters and the gradient with the step characteristics. The physical model simulation used step gradient with 1:15 model scale, 1:1 and 1:15 gradient, and step segment angle variation θ, which was 60, 90 and 120. A measurement to the wave height was taken in front of the model and the occurring run-up and run-down height. The height on the step gradient was then compared to the soft and impermeable slope gradient model. The model was made from triplex wood with 15 cm width and 45 cm height. Step construction was placed on 9 m distance in front of the channel and in the middle of flume width. Observation was taken for various depth d, wave height H, and period T. Results of the study showed that the influencing parameters on the occurring run-up and run-down height on the step gradient was influenced by the period (T), incoming wave height (H), and water depth (d), the structure wall ramp (α), angle formed by the step segment (θ) and the step segment height (s). At step segment angle of 1200, the run-up and run-down wave height were relatively smaller than 600 and 900 step segment angle, respectively. On the soft and impermeable slope gradient, higher incoming wave indicated higher run-up and run-down. On the step gradient, higher incoming wave indicated relatively declining run-up and run-down height, although the height variation was not large enough.